ISLAMIC ECONOMIC REVIEW ON THE IMPLEMENTATION OF MUDHARABAH MUTHLAQOH AGREEMENTS IN INDONESIAN HAJJ SAVINGS PRODUCTS AT BSI (BANK SYARIAH INDONESIA) M. KHOLIL BANGKALAN BRANCH - Rasidi, Yusuf Pandu; Hasan, Dony Burhan Noor (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Abstract: The research with the title